2010
DOI: 10.1080/10790268.2010.11689715
|View full text |Cite
|
Sign up to set email alerts
|

Soleus H-Reflex Modulation After Motor Incomplete Spinal Cord Injury: Effects of Body Position and Walking Speed

Abstract: Objective: To examine position-dependent (semireclined to standing) and walking speed-dependent soleus H-reflex modulation after motor incomplete spinal cord injury (SCI). Participants: Twenty-six patients with motor incomplete SCI (mean: 45 ± 15 years) and 16 noninjured people (mean: 38 ± 14 years). Methods: Soleus H-reflexes were evoked by tibial nerve stimulation. Patients were tested in semireclined and standing positions (experiment 1) and in midstance and midswing positions (experiment 2).Results: H-refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…As a reason for increase of H-reflexes during standing, supraspinal centers might hardly modulate the H-reflexes and MLR during static standing, and the stance and swing phases during walking in those patients 18,[48][49][50] . Nardone et al 50) has shown that Achilles' tendon vibration increases the SLR and MLR activities of Sol of hemiparetic patients with spastic hypertonia due to a loss of descending control from supraspinal centers on group Ia and II reflex pathways.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As a reason for increase of H-reflexes during standing, supraspinal centers might hardly modulate the H-reflexes and MLR during static standing, and the stance and swing phases during walking in those patients 18,[48][49][50] . Nardone et al 50) has shown that Achilles' tendon vibration increases the SLR and MLR activities of Sol of hemiparetic patients with spastic hypertonia due to a loss of descending control from supraspinal centers on group Ia and II reflex pathways.…”
Section: Discussionmentioning
confidence: 96%
“…In patients with spastic or spinal cord injury that have standing balance impairment and gait disturbance, the Sol H-reflex is increased compared to healthy subjects 19,48,49) . As a reason for increase of H-reflexes during standing, supraspinal centers might hardly modulate the H-reflexes and MLR during static standing, and the stance and swing phases during walking in those patients 18,[48][49][50] .…”
Section: Discussionmentioning
confidence: 98%
“…4 Because walkers are routinely prescribed to assist with locomotion in the SCI population, it is important to understand the neurophysiological impact of walker use. The first step in developing a deeper understanding is to assess the reflexes of individuals with SCI walking with and without a walker.…”
Section: Proffered Papermentioning
confidence: 99%
“…3 Modulation of soleus H-reflexes is highly task specific; there is smaller reflex size during standing compared to the semi-reclined position. 4 Similarly, the reflex size is significantly smaller (or absent) during the swing phase compared to the stance phase of walking in non-injured individuals. 4 Although the H-reflex modulation is impaired after SCI, it is not clear what specific aspects of standing and walking such as afferent activation and loading during use of assistive devices most directly affect reflex modulation.…”
mentioning
confidence: 97%
“…Craven and Morris (2010) found the intra-rater reliability for the MAS to be fair-to-perfect (0.20<k<1.0), and inter-rater reliability was found to be poor-to-moderate (k<0.60) [12][13][14] . Although measures of reliability are low, there is evidence to suggest that a change in MAS scores indicates a change in muscle spindle excitability [15] and level of excitation at the spinal cord neurons [16] . MAS remains the primary choice for clinicians to measure spasticity.…”
Section: Modified Ashworth Scale (Mas)mentioning
confidence: 99%